(untitled) (Web of Teachers: Inderscience Research, 2024)
This article deals with the issues of execution of peculiarities of documents intended to be sent abroad. It can be noted that in recent years in our country are economic reforms that stimulate business interest in Uzbekistan on the part of foreign investors, a noticeable increase in the number of notarial acts performed with the participation or in the interests of foreign legal entities